A meta‐analysis on the influence of partial biopsy of primary melanoma on disease recurrence and patient survival. (15th September 2019) - Moscarella, E.; Pampena, R.; Palmiotti, G.; Bonamonte, D.; Brancaccio, G.; Piccolo, V.; Longo, C.; Argenziano, G.
Abstract: Background: Complete surgical excision is the preferred biopsy type for suspicious melanocytic lesions. However, partial biopsy is sometimes used in special situations. Previous studies have explored the effect of partial biopsy of a primary melanoma on patient outcome with controversial results. Objective: We performed a meta‐analysis on the influence of the type of biopsy of a primary melanoma on recurrence‐free survival (RFS) and melanoma‐related survival (MRS). Methods: Clinical trials, observational cohort studies and case–control studies reporting absolute number of recurrences and/or melanoma‐related deaths in patients undergoing a partial or excisional biopsy of melanoma were included in the meta‐analysis. Results: In all, the five included studies reported 3249 patients, 1121 (34.5%) of them in the partial biopsy group and 2128 (65.5%) in the excisional biopsy group. Despite a trend in favour of excisional biopsy in reducing the risk for recurrences, the forest plot related to RFS failed to demonstrate significant differences among groups (RR: 1.27; 95% CI 0.97–1.67; P : 0.09; random effects; I 2 : 55%). The forest plot showed no difference in the risk of dying for melanoma‐related causes for patients undergoing partial biopsy vs. excisions biopsy (RR: 1.50; 95% CI 0.98–2.30; P : 0.06; random effects; I 2 : 60%). Limitations: The majority of the studies were retrospective, and follow‐up time was not uniform among studies and not always reported. Conclusion: In conclusion, a partial biopsy can be performed in special situations, such as large primary tumours located in surgically sensitive areas, without altering MRS and RFS.